GMO Labeling Policy and Consumer Choice. (May 2022) - Kim, Youngju; Kim, SunAh; Arora, Neeraj
Most scientists claim that genetically modified organisms (GMOs) in foods are safe for human consumption and offer societal benefits such as better nutritional content. However, many consumers remain skeptical about their safety. Against this backdrop of diverging views, the authors investigate the impact of different GMO labeling policy regimes on the products consumers choose. Guided by the literature on negativity bias, structural alignment theory, and message presentation, and based on findings from four experiments, the authors show that consumer demand for GM foods depends on the labeling regime policy makers adopt. Both absence-focused ("non-GMO") and presence-focused ("contains GMO") labeling regimes reduce the market share of GM foods, with the reduction being greater in the latter case. GMO labels reduce the importance consumers place on price and enhance their willingness to pay for non-GM products. Results indicate that specific label design choices policy makers implement (in the form of color and style) also affect consumer responses to GM labeling. Consumer attitudes toward GMOs moderate this effect—consumers with neutral attitudes toward GMOs are influenced most significantly by the label design.